Foreign direct investment and economic complexity in emerging economies - Tolulope T. Osinubi; Folorunsho M. Ajide (Universitas Islam Indonesia, 2022)
Purpose ― In this study, we investigate the impact of foreign direct investment (FDI) on economic complexity in MINT and BRICS countries. Methodology ― Data on economic complexity from MIT’s Observatory of Economic Complexity and data on FDI and other determinants of economic complexity are sourced from World Development indicators which spanned between 1991 and 2020. The countries are divided into three categories: All countries pooled together, MINT and BRICS countries. We employ panel co-integrating regression. Findings ― Findings based on panel co-integration regression show that foreign direct investment positively impacts economic complexity in all the countries and MINT countries, while its impact is negative in BRICS countries. Originality ― This study adds value to the literature by scrutinizing the nexus between FDI and economic complexity in the context of emerging economies and employs the panel co-integration technique for robust analysis. The study's findings shed light on the need for governments in developing countries to implement appropriate policies encouraging FDI inflows into their respective countries. Contributing to the host country's economic complexity, FDI inflows should be focused on highly technical investment and, most importantly, should be selective to enhance the development of priority sectors. An investment promotion policy may be required to encourage foreign investment in the host country.